Method for modifying solid electrolyte-high-voltage positive electrode interface through double-filler doped interface buffer layer
By using the doped buffer layer formed by LiPO2F2 and fullerene C60 in the solid-state electrolyte-high voltage positive electrode interface, the problems of poor interface compatibility and insufficient structural stability are solved, and the length of NCM811 positive electrode and electrolyte at high voltage is achieved. Improved cycle life, suitable for high voltage solid-state batteries.
Patent Information
- Application Number
- CN202411224465.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-03
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-03
AI Technical Summary
Solid-state electrolyte-high voltage positive electrode has poor interface compatibility, high interface impedance and space charge layer effect limit the electrochemical performance of high-voltage solid-state batteries. The existing buffer layer modification method is difficult to improve the structural stability of the positive electrode and electrolyte at high voltages. .
Using a double filler doped interface buffer layer, a thin and uniform CEI film rich in LixPOyFz, LiPxFy and C60Fn is spontaneously formed on the surface of NCM811 particles through the synergistic action of LiPO2F2 and fullerene C60, improving interface contact and structural stability.
It effectively improves the structural stability of the NCM811 positive electrode and electrolyte during the cycle process, extends the cycle life of LATP-based high-voltage solid-state batteries, and simplifies the preparation process, which is suitable for large-scale applications of high-voltage solid-state batteries.
Smart Images

Figure CN119208718A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of material preparation and application, and more specifically, relates to a dual filler (LiPO2F2 and fullerene C 60 ) A method for modifying the solid electrolyte-high voltage positive electrode interface by doping the interface buffer layer. Background Art
[0002] Since the 1990s, lithium-ion batteries have been widely used in portable electronic devices and new energy vehicles due to their advantages such as high energy density, long cycle life and no memory effect. However, there are still problems such as poor cycle performance and insufficient safety, which cannot meet commercial needs. Solid-state batteries based on high-voltage layered oxide cathodes have high energy density and high safety and have broad application prospects. However, problems such as poor interfacial compatibility between solid electrolyte and high-voltage cathode, high interfacial impedance caused by poor contact, and the existence of space charge layer effect limit the electrochemical performance of the battery. Therefore, improving the solid electrolyte-high-voltage cathode interface is of great significance to promote the development and application of high-voltage solid-state batteries.
[0003] Adding a buffer layer at the high voltage positive electrode-solid electrolyte interface is an effective solution to alleviate the rigid "point-to-point" contact of the interface. CN117747957A discloses a nitrile-containing solidifying liquid for modifying the solid electrolyte-positive electrode interface, which enhances the interface contact, improves the ion transmission at the interface, and improves the cycle stability and rate performance of the battery.
[0004] Although the above modification methods have improved the solid electrolyte-cathode interface contact problem to a certain extent, the structural stability of the cathode and electrolyte is difficult to improve under high voltage. Summary of the invention
[0005] Based on the shortcomings of the prior art, the present invention discloses a method for modifying the interface of a solid electrolyte and a high voltage positive electrode by doping an interface buffer layer with double fillers, and the interface buffer layer contains LiPO2F2 and fullerene C 60 The synergistic effect of NCM811 particles spontaneously forms a layer rich in Li x PO y F z , LiP x F y and C 60 F n The thin and uniform CEI film effectively improves the structural stability of the NCM811 cathode and electrolyte during the cycle process, and enhances the long cycle life of the LATP-based high-voltage solid-state battery.
[0006] The present invention includes the following technical solutions:
[0007] A method for modifying the interface of a solid electrolyte and a high voltage positive electrode by doping an interface buffer layer with dual fillers, characterized in that the polymer matrix of the interface buffer layer is PEO, and the dual fillers are LiPO2F2 and fullerene C 60 , the solid electrolyte is Li 1.4 Al 0.4 Ti 1.6 (PO4)3(LATP), the positive electrode material is NCM811, and the preparation method includes the following steps:
[0008] S1. Prepare the precursor solution by dissolving PEO and LiTFSI in acetonitrile, and then add LiPO2F2 and fullerene C 60 , heat and stir evenly;
[0009] S2. The precursor solution obtained in step S1 is evenly applied to the surface of the LATP sheet by a pipette, and then placed in an oven to form a film under vacuum to obtain an interface buffer layer;
[0010] S3. Attach the NCM811 electrode to the other side of the interface buffer layer.
[0011] Furthermore, in the above method of modifying the solid electrolyte-high voltage positive electrode interface by doping an interface buffer layer with dual fillers, the molar ratio of PEO monomer to LiTFSI in step S1 is 20:1.
[0012] Furthermore, in the above method for modifying the solid electrolyte-high voltage positive electrode interface by doping the interface buffer layer with dual fillers, the heating and stirring temperature in step S1 is 60° C., and the stirring speed is 800-1000 rpm.
[0013] Furthermore, in the above method for modifying the solid electrolyte-high voltage positive electrode interface by a dual-filler doped interface buffer layer, the vacuum drying temperature in step S2 is 60° C. and the time is 12 hours.
[0014] Furthermore, in the above-mentioned method of modifying the solid electrolyte-high voltage positive electrode interface by a dual-filler doped interface buffer layer, the LATP sheet in step S2 is synthesized by a solid phase method.
[0015] Furthermore, in the above-mentioned method of modifying the solid electrolyte-high voltage positive electrode interface by a dual filler doped interface buffer layer, the LATP sheet in step S2 is synthesized by the following method:
[0016] Li2CO3, NH4H2(PO4)3, TiO2 and Al2O3 are weighed according to the stoichiometric ratio; preferably, (Li2CO3 is in excess of 5% to compensate for the loss of lithium); and the mixture is ball-milled for 2 hours using anhydrous ethanol as a ball-milling medium to obtain a uniform slurry. After the slurry is dried, it is placed in an oven at 180°C for 7 days and then calcined at 700°C for 4 hours to obtain an initial powder. The initial powder is ball-milled for a second time for 8 hours to obtain a uniform slurry. After the uniform slurry is dried, it is granulated and pressed into sheets with a diameter of 12 mm and sintered at 900°C for 6 hours to obtain LATP sheets with a diameter of about 10 mm.
[0017] Furthermore, in the above method for modifying the solid electrolyte-high voltage positive electrode interface by a dual filler doped interface buffer layer, the NCM811 pole piece in step S3 is prepared by the following steps:
[0018] The positive electrode material NCM811 and the active materials acetylene black and PVDF were mixed in a NMP solution at a mass ratio of 8:1:1, stirred overnight, coated on aluminum foil, and placed in a vacuum drying oven at 80° C. and dried for 12 hours.
[0019] Furthermore, in the above-mentioned method for modifying the interface of a solid electrolyte-high voltage positive electrode by doping an interface buffer layer with dual fillers, the loading amount of NCM811 in the NCM811 pole piece is 2 mg cm -2 .
[0020] The present invention also discloses a solid electrolyte-high voltage positive electrode interface, which is prepared by any of the methods described above.
[0021] The present invention also discloses the use of the above preparation method in preparing a long cycle life LATP-based high-voltage solid-state battery.
[0022] Compared with the prior art, the present invention has the following outstanding beneficial effects:
[0023] The present invention discloses a method for modifying the interface of a solid electrolyte and a high voltage positive electrode by using a double filler doped interface buffer layer. The present invention introduces a thin double filler doped interface buffer layer between the LATP-NCM811 interface to achieve the spontaneous formation of a layer rich in Li on the surface of NCM811 particles. x PO y F z , LiP x F y and C 60 F n The CEI membrane effectively improves the structural stability of the NCM811 cathode and electrolyte during the cycle process, and improves the long cycle life of the LATP-based high-voltage solid-state battery. The preparation method of the present invention is simple, can be prepared on a large scale, and has a wide range of application scenarios in the field of high-voltage solid-state batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 TEM images of the NCM811 positive electrode after 150 cycles of the battery in Comparative Example 1, Comparative Example 2 and Example 1;
[0025] Figure 2 This is an XPS graph of the NCM811 positive electrode after 150 cycles of a battery in Example 1;
[0026] Figure 3 This is a comparison chart of the 150-cycle performance of the battery in Comparative Example 1 and Example 1 at a voltage range of 2.7-4.3V and a current density of 0.5C;
[0027] Figure 4 It is a comparison chart of the rate performance of the batteries in comparative example 1 and embodiment 1. DETAILED DESCRIPTION
[0028] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] Embodiment 1
[0030] 1. Prepare the precursor solution by dissolving 0.25g PEO and 0.09g LiTFSI in 5mL acetonitrile, and then add 0.017g LiPO2F2 and 0.017g C 60 , heat and stir evenly, the temperature during heating and stirring is 60℃, and the stirring speed is 800-1000r min -1 ;
[0031] 2. Use a pipette to take 30 μL of the precursor slurry obtained in 1 and evenly drop it on the surface of the LATP sheet, and place it in a 60°C oven under vacuum and dry it for 12 hours to form a film;
[0032] 3. Attach the NCM811 electrode to the other side of the interface buffer layer.
[0033] Embodiment 2
[0034] 1. Prepare the precursor solution by dissolving 0.25g PEO and 0.09g LiTFSI in 5mL acetonitrile, and then add 0.017g LiPO2F2 and 0.003g C 60 , heat and stir evenly; the temperature during heating and stirring is 60℃, and the stirring speed is 800-1000r min -1 ;
[0035] 2. Use a pipette to take 30 μL of the precursor slurry obtained in 1 and evenly drop it on the surface of the LATP sheet, and place it in a 60°C oven under vacuum and dry it for 12 hours to form a film;
[0036] 3. Attach the NCM811 electrode to the other side of the interface buffer layer.
[0037] Embodiment 3
[0038] 1. Prepare the precursor solution by dissolving 0.25g PEO and 0.09g LiTFSI in 5mL acetonitrile, and then add 0.017g LiPO2F2 and 0.010g C 60 , heat and stir evenly; the temperature during heating and stirring is 60℃, and the stirring speed is 800-1000r min -1 ;
[0039] 2. Use a pipette to take 30 μL of the precursor slurry obtained in 1 and evenly drop it on the surface of the LATP sheet, and place it in a 60°C oven under vacuum and dry it for 12 hours to form a film;
[0040] 3. Attach the NCM811 electrode to the other side of the interface buffer layer.
[0041] Embodiment 4
[0042] 1. Prepare the precursor solution by dissolving 0.25g PEO and 0.09g LiTFSI in 5mL acetonitrile, and then add 0.017g LiPO2F2 and 0.031g C 60 , heat and stir evenly; the temperature during heating and stirring is 60℃, and the stirring speed is 800-1000r min -1 ;
[0043] 2. Use a pipette to take 30 μL of the precursor slurry obtained in 1 and evenly drop it on the surface of the LATP sheet, and place it in a 60°C oven under vacuum and dry it for 12 hours to form a film;
[0044] 3. Attach the NCM811 electrode to the other side of the interface buffer layer.
[0045] Comparative Example 1
[0046] 1. Prepare the precursor solution by dissolving 0.25g PEO and 0.09g LiTFSI in 5mL acetonitrile, and heat and stir evenly; the temperature during heating and stirring is 60℃, and the stirring speed is 800-1000r min -1 ;
[0047] 2. Use a pipette to take 30 μL of the precursor slurry obtained in 1 and evenly drop it on the surface of the LATP sheet, and place it in a 60°C oven under vacuum and dry it for 12 hours to form a film;
[0048] 3. Attach the NCM811 electrode to the other side of the interface buffer layer.
[0049] Comparative Example 2
[0050] 1. Prepare the precursor solution by dissolving 0.25g PEO and 0.09g LiTFSI in 5mL acetonitrile, then add 0.017g LiPO2F2 in turn, and heat and stir evenly; the temperature during heating and stirring is 60℃, and the stirring speed is 800-1000r min -1 ;
[0051] 2. Use a pipette to take 30 μL of the precursor slurry obtained in 1 and evenly drop it on the surface of the LATP sheet, and place it in a 60°C oven under vacuum and dry it for 12 hours to form a film;
[0052] 3. Attach the NCM811 electrode to the other side of the interface buffer layer.
[0053] Comparative Example 3
[0054] 1. Prepare the precursor solution by dissolving 0.25g PEO and 0.09g LiTFSI in 5mL acetonitrile, and then add 0.017g C 60 , heat and stir evenly; the temperature during heating and stirring is 60℃, and the stirring speed is 800-1000r min -1 ;
[0055] 2. Use a pipette to take 30 μL of the precursor slurry obtained in 1 and evenly drop it on the surface of the LATP sheet, and place it in a 60°C oven under vacuum and dry it for 12 hours to form a film;
[0056] 3. Attach the NCM811 electrode to the other side of the interface buffer layer.
[0057] Test Case
[0058] The above-mentioned embodiments and comparative examples were applied as solid electrolyte-high voltage positive electrode interface buffer layers in high voltage solid-state batteries for performance testing.
[0059] Figure 1 TEM images of the NCM811 positive electrode after 150 cycles of the battery in Comparative Example 1, Comparative Example 2 and Example 1. Figure 1 It can be seen that due to LiPO2F2 and C 60 Due to the synergistic effect, a uniform and thin CEI film is formed on the surface of NCM811 positive electrode particles. Figure 2 This is the XPS graph of the NCM811 positive electrode after 150 cycles of the battery in Example 1. It can be seen that the CEI film composition on the surface of the NCM811 particles in Example 1 is Li x PO y Fz , LiP x F y and C 60 F n . Figure 3 Cycle performance and Figure 4 The rate performance shows that LiPO2F2 and C 60 The electrochemical performance of the battery was improved after the dual-doped buffer layer was modified.
[0060] The long cycle performance of the batteries in the embodiments of the present invention and the comparative examples was tested, and the results are shown in Table 1.
[0061] Table 1 Long cycle performance of the battery in the embodiment and comparative example at a voltage range of 2.7-4.3V and a current density of 0.5C
[0062]
[0063]
[0064] Note: The capacity retention rate is the ratio of the 150-cycle discharge capacity to the first-cycle discharge capacity.
[0065] From the above embodiments and test examples, it can be seen that the present invention uses LiPO2F2 and fullerene C in the interface buffer layer to form a 60 The synergistic effect of NCM811 particles spontaneously forms a layer rich in Li x PO y F z , LiP x F y and C 60 F n The thin and uniform CEI film effectively improves the structural stability of the NCM811 cathode and electrolyte during the cycle process, and improves the long cycle life of the LATP-based high-voltage solid-state battery. The preparation method of the present invention is simple, can be prepared on a large scale, and has a wide range of application scenarios in the field of high-voltage solid-state batteries.
[0066] The above are only a few preferred embodiments of the present invention, which are described in a more specific and detailed manner, but they cannot be understood as limiting the scope of the present invention. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A method for modifying the interface of a solid electrolyte and a high voltage positive electrode by doping an interface buffer layer with dual fillers, characterized in that: The polymer matrix of the interface buffer layer is PEO, and the dual fillers are LiPO2F2 and fullerene C 60 , the solid electrolyte is Li 1.4 Al 0.4 Ti 1.6 (PO4)3 (LATP), the positive electrode material is NCM811, and the preparation method includes the following steps: S1. Prepare the precursor solution by dissolving PEO and LiTFSI in acetonitrile, and then add LiPO2F2 and fullerene C 60 , heat and stir evenly; S2. The precursor solution obtained in step S1 is evenly applied to the surface of the LATP sheet by a pipette and placed in a vacuum oven to form a film to obtain an interface buffer layer; S3. Attach the NCM811 electrode to the other side of the interface buffer layer.
2. The method for modifying the solid electrolyte-high voltage positive electrode interface by a dual filler doped interface buffer layer according to claim 1, characterized in that: The molar ratio of PEO monomer to LiTFSI in step S1 is 20:
1.
3. The method for modifying the solid electrolyte-high voltage positive electrode interface by a dual filler doped interface buffer layer according to claim 1, characterized in that: The heating and stirring temperature in step S1 is 60° C., and the stirring speed is 800-1000 rpm.
4. The method for modifying the solid electrolyte-high voltage positive electrode interface by a dual filler doped interface buffer layer according to claim 1, characterized in that: The vacuum drying temperature in step S2 is 60° C. and the time is 12 h.
5. The method for modifying the solid electrolyte-high voltage positive electrode interface by a dual filler doped interface buffer layer according to claim 1, characterized in that: The LATP sheet in step S2 is synthesized by solid phase method.
6. The method for modifying the solid electrolyte-high voltage positive electrode interface by a dual filler doped interface buffer layer according to claim 5, characterized in that: The LATP sheet in step S2 is synthesized by the following method: Li2CO3, NH4H2(PO4)3, TiO2 and Al2O3 were weighed according to the stoichiometric ratio; and the mixture was ball-milled for 2 h using anhydrous ethanol as the ball-milling medium to obtain a uniform slurry. After the slurry was dried, it was placed in an oven at 180 ℃ for 7 days and then calcined at 700 ℃ for 4 h to obtain an initial powder. The initial powder was ball-milled for a second time for 8 h to obtain a uniform slurry. After the uniform slurry was dried, it was granulated and pressed into sheets with a diameter of 12 mm and sintered at 900 ℃ for 6 h to obtain LATP sheets with a diameter of about 10 mm.
7. The method for modifying the solid electrolyte-high voltage positive electrode interface by a dual filler doped interface buffer layer according to claim 1, characterized in that: The NCM811 pole piece in step S3 is prepared by the following steps: The positive electrode material NCM811 and the active materials acetylene black and PVDF were mixed in a NMP solution in a mass ratio of 8:1:1 and stirred overnight, then coated on aluminum foil and dried in a vacuum drying oven at 80°C for 12 h.
8. The method for modifying the solid electrolyte-high voltage positive electrode interface by a dual filler doped interface buffer layer according to claim 7, characterized in that: The NCM811 loading in the NCM811 pole piece is 2 mg cm -2 .
9. A solid electrolyte-high voltage positive electrode interface, characterized in that The method is prepared by any one of claims 1 to 8.
10. Use of the method according to any one of claims 1 to 8 in preparing a long cycle life LATP-based high voltage solid-state battery.
Citation Information
Patent Citations
Electrolyte, battery using same and method of use of same, and electrolyte production method
CN102405551A
Solid-state battery negative electrode manufacturing method and solid-state battery negative electrode
CN115986061A
Solid-state battery applying fullerene modified solid-state polymer electrolyte and preparation method of solid-state battery
CN118431553A
Solid state electrolyte composites based on complex hydrides and metal doped fullerenes / fulleranes for batteries and electrochemical applications
US20140356732A1
Electrolyte containing solid particles and lithium ion secondary battery
US20230047398A1
Cited By
High-voltage-resistant cross-linked polymer solid electrolyte and preparation method thereof
CN121172232A
Modified pEO-based solid-state electrolyte and preparation method and application thereof
CN122992166A